Analyzing Validity and Reliability of Malaysian Building Surveyor Graduates Competency - Model Survey Instrument using the Rasch Measurement Model - Hamidah Husain, Siti; Mohd Affandi, Haryanti; Irfan Che-Ani, Adi; Mohamad Nasri, Nurfaradilla (International Journal of Engineering and Technology, 2018)
The competency assessment instrument is a newly developed standard guideline for Malaysian building surveyor graduates in assessing their competency. In developing this competency assessment, researchers used a form of instrument survey in identifying the required competency domains for Malaysian building surveyor graduates. This study was conducted to examine the validity and reliability of the item contained in this competency assessment instrument. The instrument was designed using a 4 Likert scale was employed for data collection process which consists of 48 items with seven constructs representing non-technical competency domains. Â Meanwhile, 155 items with 14 constructs representing technical competency domains. A total of 56 building surveyor practitioners participated in this study. The results obtained were analyzed using the Rasch measurement model with a WinSteps version 3.73 to examine the item and person reliability. Additionally, the item measure quality was assessed by analyzing the PTMea Corr, infit and outfit MNSQ and ZSTD values to examine the construct validity. The results showed that the reliability of instrument items was 0.76 and the person reliability index was 0.93 which show that this instrument is reliable and acceptable with a high level of consistency for measuring the competence domains required from building surveyor graduates. While all the PTMEA Corr is in positive values which show that the item can differentiate the ability of the respondent. The final result relieved that out of 203 items, 13 items suggested being eliminated and revealed 190 items that are suitable to measure the 21 constructs in this competency assessment instrument.Â Â Â Â Â